Eligibility to Use the Fund's Facilities for Concessional Financing : Republic of South Sudan. (Policy Papers; Policy Paper ;, 2012)
Having become a Fund member in April 2012, South Sudan can now be considered for PRGT eligibility. In February 2012, the Executive Board reviewed the framework for eligibility to use the Fund's concessional financing facilities and the list of PRGT-eligible countries. During that review, Directors agreed to maintain the PRGT eligibility framework with a modification of the population threshold used to define small countries. Directors also decided to keep the list of PRGT-eligible countries unchanged. Under the framework to assess PRGT eligibility, decisions on entry onto the list of PRGT-eligible countries can be adopted in the period between reviews. As noted in the staff paper for the 2012 review of PRGT eligibility, given the available data, it was expected that South Sudan would be proposed for entry onto the PRGT-eligibility list after it had joined the Fund. Accordingly, this paper proposes that South Sudan now be added to the list of PRGT-eligible countries.